Reactivity and reaction products of alkali-activated, fly ash/slag paste. (15th April 2015) - Lee, N.K.; Lee, H.K.
Highlights: The amount of added slag affected the formation of reaction product. As the amount of added slag increased, the amount of C-S-H gel increased. The aluminosilicate gel with the Q4 units was similar to a Ca-based geopolymer. Abstract: Few studies have described the reaction products of an alkali-activated, two-source binder and their characteristics due to the complexity of the mechanism. In this study, the microstructure, reaction products, and reactivity of alkali-activated, fly ash/slag binders synthesized at various mixture ratios of two raw materials were examined using various experimental techniques (NMR, ICP-OES, EDS, FT-IR and TGA) to systematically investigate the complex reaction mechanism of the binders. It was also intended to help assess durability of the binders. It was found that the amount of added slag primarily affected the amount of reaction product and its silicate structure, and as the amount of added slag increased, the amount of C-S-H gel increased and the amount of aluminosilicate gel decreased. Considering chemical composition and silicate structure, the aluminosilicate gel with the Q4 ( n Al) units was found to be similar to a Ca-based geopolymer (N-C-A-S-H). The chemical composition ratios of the Ca-based geopolymer were nearly the same as those of C-S-H whereas their silicate structures were different.